2004
DOI: 10.1136/gut.2003.018911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a corticotropin releasing hormone receptor antagonist on colonic sensory and motor function in patients with irritable bowel syndrome

Abstract: Background and aims: Corticotropin releasing hormone (CRH) is a major mediator of the stress response in the brain-gut axis. Irritable bowel syndrome (IBS) is presumed to be a disorder of the brain-gut link associated with an exaggerated response to stress. We hypothesised that peripheral administration of a-helical CRH (ahCRH), a non-selective CRH receptor antagonist, would improve gastrointestinal motility, visceral perception, and negative mood in response to gut stimulation in IBS patients. Methods: Ten no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
180
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(190 citation statements)
references
References 31 publications
6
180
2
2
Order By: Relevance
“…In light of the recent increasing interest in the potential modulating effects of CRF in clinically relevant pain conditions such as visceral pain (Nozu and Kudaira, 2006;Sagami et al, 2004), postoperative joint pain (Likar et al, 2007), and fibromyalgia (McLean et al, 2006;Lund et al, 2006), we set out to investigate systematically the antinociceptive effects of CRF at the three main levels of the neuraxis of pain transmission, that is, at the level of the brain, spinal cord, and periphery. As it was suggested that antinociceptive effects of CRF are identified rather in tonic than in phasic pain (Lariviere and Melzack, 2000), we have chosen an animal model of tonic pain, that is, Freunds complete adjuvant (FCA) hindpaw inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the recent increasing interest in the potential modulating effects of CRF in clinically relevant pain conditions such as visceral pain (Nozu and Kudaira, 2006;Sagami et al, 2004), postoperative joint pain (Likar et al, 2007), and fibromyalgia (McLean et al, 2006;Lund et al, 2006), we set out to investigate systematically the antinociceptive effects of CRF at the three main levels of the neuraxis of pain transmission, that is, at the level of the brain, spinal cord, and periphery. As it was suggested that antinociceptive effects of CRF are identified rather in tonic than in phasic pain (Lariviere and Melzack, 2000), we have chosen an animal model of tonic pain, that is, Freunds complete adjuvant (FCA) hindpaw inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Central and systemic CRF and Ucns induce the symptoms of this syndrome, and antagonists blunt the effects of stress on the gut (3,4). A CRF-R1 antagonist also suppresses the colonic motility and pain responses to colonic distension and stimulation of the rectal mucosa in patients with irritable bowel syndrome (15). Additional mechanistic studies, such as that of la Fleur et al, are clearly warranted to further our understanding of the intestinal stress response system in diseases and the physiological regulation of digestion.…”
mentioning
confidence: 99%
“…18 Another study reported that when a-helical CRH was peripherally administered in IBS patients, the hyperresponsiveness to stress induced by colonic electrical stimulation was suppressed. 8 These results indicate that stress is closely associated with colonic perception and bowel movements. Previous animal studies have analyzed esophageal perception after stress loading.…”
Section: Discussionmentioning
confidence: 68%
“…6 Central and gastrointestinal responses to stress can be pronounced, particularly in patients with FGID such as IBS. 7,8,15,16 The association between stress and visceral perception has been reported in a number of colonic studies. Fukudo et al 17 showed…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation